2014
DOI: 10.1161/strokeaha.114.005535
|View full text |Cite
|
Sign up to set email alerts
|

Off-Hours Admission and Acute Stroke Care Quality

Abstract: Background and Purpose— Studies have reported higher risks of death and other adverse outcomes in acute stroke patients admitted off-hours; however, little is known about the underlying mechanisms. According to time of admission, our aim was to examine compliance with performance measures for acute stroke care processes, including the effect of a systematic quality improvement program, and to examine 30 days case-fatality. Methods— A population-based hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…[2,12,2934] However, the effect of weekend or off-hour admission on mortality has been negated after adjustment for stroke severity as assessed by using a stroke scale or a similar proxy, [4,9,10,28,35,36] as seen in the present study. The present analysis also found that the effect of brain surgery on mortality turned from harmful to null after adjustment for stroke severity.…”
Section: Discussionmentioning
confidence: 53%
“…[2,12,2934] However, the effect of weekend or off-hour admission on mortality has been negated after adjustment for stroke severity as assessed by using a stroke scale or a similar proxy, [4,9,10,28,35,36] as seen in the present study. The present analysis also found that the effect of brain surgery on mortality turned from harmful to null after adjustment for stroke severity.…”
Section: Discussionmentioning
confidence: 53%
“…A recent study of stroke care in the Denmark (using the Danish Stroke Registry) found that patients admitted during off-hours showed a lower degree of compliance with 8 out of 10 performance measures between 2003 and 2011 [ 26 ]. In contrast, our study showed that patients admitted during off-hours did not receive a poorer quality of care between 2007 and 2008 in the CNSR database.…”
Section: Discussionmentioning
confidence: 99%